Determination of Bioactive Compounds and Mineral Contents of Seedless Parts and Seeds of Grapes - Özcan, M.M.; Al Juhaimi, F.; Gülcü, M.; Uslu, N.; Geçgel, Ü. (South African Journal of Enology and Viticulture, 2017)
In this study, phenolic compounds, minerals, total flavonoids, total phenolic contents and antioxidant activities of the seedless parts (pulp+skin) and seeds of table and wine grapes were determined. Also, the total oil, tocopherol contents and fatty acid composition of seed oils of table and wine grapes were investigated. The highest total phenolic content of the grape pulp was found in Trakya ilkeren (199.063mg/100 g), while total flavonoid and antioxidant activity of the pulp was determined at a high level in Red Globe (6.810 mg/g, 90.948%). Antioxidant activity, and the total phenolic and flavonoid contents of grape seeds varied between 86.688 and 90.974%, 421.563 and 490.625 mg GAE/100 g, and 90.595 and 145.595 mg/g respectively (p < 0.05). Generally, the main phenolic compounds of all grape pulps and seeds were gallic acid, 3,4- dihydroxybenzoic acid, (+)-catechin and 1,2-dihydroxybenzene. In addition, the oil contents of grape seeds ranged from 5.275 (Çavuş) to 13.881% (Çınarlı karası) (p < 0.05). The major fatty acids of grape seed oils were linoleic, oleic and palmitic acid. The seed oil of the Trakya ilkeren variety was rich in tocopherols in comparison with the other varieties. The major minerals of both the seedless parts and the seeds were determined as K, Ca, P, S, Mg.